Trauma and cinema : cross-cultural explorations - Kaplan, E. Ann.; Wang, Ban, 1957- (Hong Kong : Hong Kong University Press, 2004)
Annotation This volume addresses the relation of trauma to transnational modern mass media. the first of its kind, Trauma and Cine.
This is my history : trauma, testimony, and nation-building in the "new" South Africa / Sarah L. Lincoln -- Traumatic contact zones and embodied translators : with reference to select Australian texts / E. Ann Kaplan -- A world of sadness? / Robert Chi -- Post-traumatic cinema and the Holocaust documentary / Joshua Hirsch -- The vicissitudes of traumatic memory and the postmodern history film / Janet Walker -- Allegorizing Hiroshima : Shindo Kaneto's Onibaba as trauma text / Adam Lowenstein -- Hiroshima, mon amour, trauma, and the sublime / Andrew Slade -- Encountering paralysis : disability, trauma, and narrative / Petra Kuppers -- To live : the survival philosophy of the traumatized / Zhaohui Xiong -- Trauma, visuality, and history in Chinese literature and film / Ban Wang.
Includes bibliographical references (pages 241-271) and index.
Print version record.
JSTOR
Keywords: Motion pictures -- History; Traumatism; War victims; Cinéma -- Histoire; Traumatisme; Victimes de guerre; PERFORMING ARTS -- Film & Video -- Reference; SOCIAL SCIENCE -- Anthropology -- Cultural; Motion pictures; Traumatism; War victims; Film; Psychisches Trauma; History; Aufsatzsammlung